Evaluación de centros y planes de mejora en Francia a partir de 2019 - Geoffray, Ghislaine; Dupuy, Linda (Avances en Supervisión Educativa, 2023)
abstract
Keywords: assessment of centers; self-evaluation; integrative evaluation; role of the inspection; evaluation reports; improvement plans